Bilateral primary vitreoretinal lymphoma masquerading as fungal endophthalmitis- a case report - Manisha Agarwal; Alankrita Muralidhar; Tanya Jain; Prashant Katre; Arpan Gandhi; Priyanka Gupta; Charu Gupta; Shishir Narain (Journal of Ophthalmic Inflammation and Infection)
Abstract Purpose To report a case of bilateral primary vitreoretinal lymphoma (PVRL) masquerading as endophthalmitis in a patient with a history of bilateral cataract surgery and COVID-19. Observation A 60-year-old male patient presented with diminution of vision in both the eyes. There was a history of bilateral cataract surgery done 2 months back at a gap of one week and COVID-19 infection treated with high dose systemic corticosteroids. Patient presented with dense vitritis with yellowish sub-retinal pigment epithelium (RPE) deposits in both the eyes six weeks after cataract surgery. It was clinically suspected to be endophthalmitis. Diagnostic vitrectomy was done in both the eyes and vitreous sample was negative on microbiological and cytological examination. Multimodal imaging along with sub retinal biopsy helped in confirming the diagnosis. Management was done using multiple intravitreal methotrexate injections and remission was achieved. Conclusion Vitritis with sub-RPE yellowish deposits may be mistaken for infectious endophthalmitis specially in a patient with a history of intraocular surgery or immunosuppression. PVRL is a great masquerader and is to be kept in mind while diagnosing a middle-aged patient with infectious or non-infectious uveitis.